OS1.7 Genomic attributes of tumor evolution and treatment response in diffuse glioma. (19th September 2018) - Lin, A L; Jonsson, P; Ogilvie, S; Chavan, S; Nolan, C; Gavrilovic, I; Kaley, T; Grommes, C; Pentsova, E; Diamond, E; Daras, M; Stone, J; et al.
Abstract: Background: Though the genomic landscape of primary gliomas has been well characterized by The Cancer Genome Atlas, the genetic determinants of malignant transformation and response to therapy remains poorly understood. Material and Methods: Prospective clinical sequencing was performed on 1, 004 gliomas from 923 patients. This dataset includes primary and recurrent tumors and contains detailed clinical annotation, including review of the patients' imaging. Results: We investigated the germline and somatic attributes of IDH1/2-wildtype and IDH1/2-mutant tumors at the time of diagnosis and recurrence. 13% of patients harbored either a pathogenic or likely pathogenic germline mutation, whereof 29% arose in genes mediating DNA repair. In astrocytomas, agnostic of IDH status, cell cycle alterations were depleted in low-grade tumors. Moreover, mutations in effectors of the cell cycle were associated with the development of enhancing disease in IDH-mutant astrocytomas but not oligodendrogliomas. IDH-mutant astrocytomas with a cell-cycle alteration have a significantly shorter progression-free survival from recurrence compared to tumors without a cell cycle alteration (median 2. 5 vs. 35. 3 months, HR 3. 25, log-rank p-value 0. 00061). Based on our data, hypermutation appears to occur exclusively in the context of pre-existing cell cycle alterations in astrocytic tumors, regardless of IDH status. We next correlated molecular findings with clinical behavior and treatment response and defined subsets of gliomas that are uniquely susceptible to targeted treatment and have a differential prognosis. Conclusion: Cell-cycle alterations are lineage-specific alterations associated with aggressive disease in glioma. Targeted genomic sequencing can identify subsets of tumors with a greater sensitivity to treatment and a better prognosis.